Sexual Dimorphism in Digit Ratios Derived from Dorsal Digit Length among Adults and Children - Kumar, Sanjay; Voracek, Martin; Singh, Maharaj (Frontiers in Endocrinology, 2017)
Sexual dimorphism in ventrally measured digit ratios (2D:4D and other) has been related to prenatal sex-hormone levels. In the present series of three studies, we measured all digit lengths (excluding the thumb) on the dorsal, rather than the ventral, side of left and right hands and investigated the sexual dimorphism in digit ratios in three independent samples, two of them comprising adults (Study I, N = 104; Study II, N = 154), and one further, comprising kindergarten children (Study III, N = 64). Results show that men have lower digit-ratio values compared to women in digit ratios that include digit 5 as one of the constituents of the ratio (i.e., the 4D:5D, 3D:5D, and 2D:5D ratios). Boys have lower values compared to girls for the 4D:5D and 3D:5D ratios, and there is a similar trend of sexual dimorphism in the 2D:5D ratio. Thus, based on the evidence from dorsally measured digit ratios, the present findings from three samples are consistent with the idea that early sex-hormonal effects might be stronger for digit ratios involving digit 5, as compared to the classic, and frequently studied, ventrally measured 2D:4D ratio.